Test of Entomopathogenic Fungus Metarhizium rileyi on Mortality of Main Pets of Cabbage (Brassica oleracea var capitata) - Muhammad Fajrul Falah; Henik Sukorini; Erfan Dani Septia; Dyah Roeswitawati; Ilmam Zul Fahmi (Universitas Muhammadiyah Palembang, 2024)
Cabbage production in 2022 in various regions in Indonesia will experience a decline, the largest decline in West Sumatra, reaching 11,005 tons. This condition is caused by a reduction in productive agricultural land and increasingly intensive attacks by plant pests. Cabbage leafworm (Plutella xylostella) and cropworm (Crocidolomia binotalis) are the main pests on cabbage plants which continue to be the main factor in reducing cabbage production. Plutella xylostella and Crocidolomia binotalis attacks, if not treated, can reduce cabbage production by up to 100%. Meanwhile, currently handling the main pests of cabbage plants still uses very excessive insecticides, both in dosage and spraying time intervals, this has a negative impact on the environment and human health. Integrated Pest Management (IPM) needs to be carried out, one of which is with entomopathogenic fungi. Metarizhium rileyi is a type of entomopathogenic fungus that efficiently and effectively controls several types of plant pests. This research aims to test the effectiveness of the entomopathogenic fungus Metarhizium rileyi against the main pests on cabbage plants in the UMM Rusunawa experimental field. This research used a simple Randomized Block Design (RBD) consisting of 2 control treatments and 3 treatments giving biological agents with various densities. The densities used in the treatment were 104 conidium/ml, 106 conidium/ml and 108 conidium/ml. Each treatment was infested with 4 cropworm larvae and 4 cabbage leafworm larvae. The results of a conidia density level of 108/ml in the Metarizhium rileyi fungus produced the highest percentage of mortality for Plutella xylostella larvae at 100% and Crocidolomia binotalis larvae at 90% and obtained the fastest time to kill 50% of test larvae (LT50) range of 2,193 days LT50 Plutella xylostella and 3,644 days LT50 Crocidolomia binotalis.